Women Safety in Digital India –a Prime Agenda for the Society - Sivapriya, C; Subhashini, S; S.Preetha, Dr (International Journal of Engineering and Technology, 2018)
In today’s world safety of women has become the greatest concern. There is no place in city in the where women are not bound to fear of violence. No leader can strongly say that his nation is free of violence on women. Women and girls face sexual harassment and threat in streets of the city, while travelling in public transport, in school & colleges. This threat has been pulling down the freedom of living a comfortable life and participating in various sectors of work and education for women. The fact is that we are unaware of the depth of problems faced by women and there are fewer laws or policies to address the issues in detail. Objective: To understand the factors that makes women feel safe in public places. To analyze the usage of Digital India in addressing the issue of women safety.